A Systematic Review on Pesticide Residue Contamination of Groundwater Coupled with Human Health Risk Assessment in Africa - Siphiwe Makamure; Lutendo Mudau; Thabiso J. Morodi; Matodzi Michael Mokoena (Adventist University of Africa, 2023)
Background: Worldwide, agriculture has become dependent on the use of pesticides to boost production and meet the demand for farm products. However, pesticide use has raised concerns about their potential harm to both ecological and human health. Prompted by this concern, a systematic literature review was conducted to assess the magnitude of pesticide residue pollution of groundwater sources, coupled with health risk assessment, in Africa. Methods: A thorough search using the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) format across multiple databases, including Science Direct, PubMed, and Google Scholar was used. Studies collected current data on groundwater pesticide residue contamination and human health risks between 2018 and September 2022. Results: Four articles distributed at four study sites in three countries were identified. Pesticide residues were distributed as 53.2% organochlorines, 21.3% organophosphates, 17.0% pyrethroids, 4.3% carbamates, and 4.3% triazines from agricultural farms. Banned organochlorines pose both carcinogenic and non-carcinogenic risks to humans, thus indicating a public health concern. Research gaps were observed in investigating herbicides and fungicides and the absence of pesticide limits in national water quality guidelines. Conclusion: The study concluded that banned organochlorine residues deteriorate groundwater quality and pose human health risks via ingestion. Therefore, there is a need for future research efforts to continue monitoring while prioritizing evaluating a wide range of pesticide residues and developing national standards for context-specific thresholds. Ultimately, sustainable agriculture is promoted, and sustainable development goals are met.